Generation of two-cell cloned embryos from mouse faecal cell. Issue 1 (December 2018) - Kamimura, Satoshi; Wakayama, Sayaka; Kuwayama, Hiroki; Tanabe, Yoshiaki; Kishigami, Satoshi; Wakayama, Teruhiko
Abstract Cloning animals using nuclear transfer (NT) provides the opportunity to preserve endangered species. However, there are risks associated with the collection of donor cells from a body, which may cause accidental death of the animal. Here, we tried to collect faeces-derived cells and examined the usability of those nuclei as a donor for NT. A relatively large number of cells could be collected from GFP-Tg mouse faeces by this method. After NT, only 4.2% of the reconstructed oocytes formed pseudo-pronucleus. This rate increased up to 25% when GFP and Hoechst were used as a marker to select better cells. However, the reconstructed oocytes/embryos showed several abnormalities, such as shrunken nuclear membranes and abnormal distribution of tubulin, and none of them developed beyond one-cell stage embryos. These developmental failures were caused by not only toxic substances derived from faeces but also intrinsic DNA damage of donor cell nuclei. However, when the serial NT was performed, some of the cloned embryos could develop to the two-cell stage. This method may remove toxic substances and enhance DNA repair in the oocyte cytoplasm. Thus, these results indicate that faeces cells might be useful for the conservation of endangered species when technical improvements are achieved.